Correction: Mohapatra et al. A Pragmatic Investigation of Energy Consumption and Utilization Models in the Urban Sector Using Predictive Intelligence Approaches. Energies 2021, 14, 3900 - Sunil Kumar Mohapatra; Sushruta Mishra; Hrudaya Kumar Tripathy; Akash Kumar Bhoi; Paolo Barsocchi (Energies, 2025)
There was an error in the original publication [...]